Combinatorial chemistry an online journal. (Elsevier Science, 1998)
A WWW only publication which contains articles on combinatorial chemistry accepted for publication in: Tetrahedron, Tetrahedron Letters, Tetrahedron:Asymmetry, Bioorganic & Medicinal Chemistry, Bioorganic & Medicinal Chemistry Letters, CarbohydrateResearch, and other relevant Elsevier Science journals. It also features specially commissioned topical reports, as well as abstracts of articles from other publications. Articles are designated with page number and are published continuously in annual volumes.